An indole alkaloid from a tribal folklore inhibits immediate early event in HSV-2 infected cells with therapeutic efficacy in vaginally infected mice. - Paromita Bag; Durbadal Ojha; Hemanta Mukherjee; Umesh Chandra Halder; Supriya Mondal; Nidhi S Chandra; Suman Nandi; Ashoke Sharon; Mamta Chawla Sarkar; Sekhar Chakrabarti; Debprasad Chattopadhyay (PLoS ONE)
Herpes genitalis, caused by HSV-2, is an incurable genital ulcerative disease transmitted by sexual intercourse. The virus establishes life-long latency in sacral root ganglia and reported to have synergistic relationship with HIV-1 transmission. Till date no effective vaccine is available, while the existing therapy frequently yielded drug resistance, toxicity and treatment failure. Thus, there is a pressing need for non-nucleotide antiviral agent from traditional source. Based on ethnomedicinal use we have isolated a compound 7-methoxy-1-methyl-4,9-dihydro-3H-pyrido[3,4-b]indole (HM) from the traditional herb Ophiorrhiza nicobarica Balkr, and evaluated its efficacy on isolates of HSV-2 in vitro and in vivo. The cytotoxicity (CC50), effective concentrations (EC50) and the mode of action of HM was determined by MTT, plaque reduction, time-of-addition, immunofluorescence (IFA), Western blot, qRT-PCR, EMSA, supershift and co-immunoprecipitation assays; while the in vivo toxicity and efficacy was evaluated in BALB/c mice. The results revealed that HM possesses significant anti-HSV-2 activity with EC50 of 1.1-2.8 µg/ml, and selectivity index of >20. The time kinetics and IFA demonstrated that HM dose dependently inhibited 50-99% of HSV-2 infection at 1.5-5.0 µg/ml at 2-4 h post-infection. Further, HM was unable to inhibit viral attachment or penetration and had no synergistic interaction with acyclovir. Moreover, Western blot and qRT-PCR assays demonstrated that HM suppressed viral IE gene expression, while the EMSA and co-immunoprecipitation studies showed that HM interfered with the recruitment of LSD-1 by HCF-1. The in vivo studies revealed that HM at its virucidal concentration was nontoxic and reduced virus yield in the brain of HSV-2 infected mice in a concentration dependent manner, compared to vaginal tissues. Thus, our results suggest that HM can serve as a prototype to develop non-nucleotide antiviral lead targeting the viral IE transcription for the management of HSV-2 infections.